The neighbors we want : a novel - Lane, Tim (Timothy S.) (Crooked Lane Books, 2023)
"Adam is having a hard time adjusting to the stay-at-home-dad life. The sleepless nights and the constant diaper changing are not what he expected after he was abruptly fired from his job. Then again, Adam wasn't prepared for his relationship with his wife Sarah to slowly come apart at the seams either. One thing, however, keeps him going--his growing obsession with his neighbor, Ali. But one night, something changes. While staying up with his baby, instead of seeing Ali in the window across the way, he sees her ex-boyfriend, Crispin, lurking around her house before disappearing within. When Adam hears that Ali doesn't show up for work the next day, and she doesn't seem to be home, he fears the worst--that she's been abducted, or possibly killed. His search for the truth will lead Adam on a path filled with deceit and lies. Adam knows the answers are lurking somewhere in the shadows of his small suburban town--the trouble is, the truth is hard to find when everyone has something to hide" --